Electrohydraulic lithotripsy for the treatment of stone impacted in a lumen-apposing metal stent in a patient with endoscopic cholecystoduodenostomy - Guzmán-Calderón, Edson (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.